2016
DOI: 10.1017/s0022215116009750
|View full text |Cite
|
Sign up to set email alerts
|

The value of close monitoring in vestibular rehabilitation therapy

Abstract: The small sample size is a major limitation; nevertheless, closely monitored vestibular rehabilitation therapy resulted in improved performance status. More studies are needed to establish the efficiency of vestibular rehabilitation therapy and compare closely monitored therapy with tailored home exercise rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Two studies (Ertugrul and Emre Soylemez,173 level II; Itani et al,179 level III) did not find an effect of age on rehabilitation outcomes for individuals with various peripheral vestibular disorders. Lorin et al213 (level IV) reported that increasing age was not associated with functional outcomes after VPT.…”
Section: Update and Revision Of Guidelinesmentioning
confidence: 94%
See 2 more Smart Citations
“…Two studies (Ertugrul and Emre Soylemez,173 level II; Itani et al,179 level III) did not find an effect of age on rehabilitation outcomes for individuals with various peripheral vestibular disorders. Lorin et al213 (level IV) reported that increasing age was not associated with functional outcomes after VPT.…”
Section: Update and Revision Of Guidelinesmentioning
confidence: 94%
“…Three studies evaluated the effect of gender on the efficacy of VPT, and none demonstrated a significant effect of gender on recovery. One level III study found no effect of gender on multiple vestibular rehabilitation outcomes in individuals with BVH112 and 2 other level III studies found no effect of gender on DGI (Itani et al179) or DHI (Ertugrul and Emre Soylemez173) scores in individuals with various peripheral vestibular disorders.…”
Section: Update and Revision Of Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, more specific approaches were used based on physiological or behavioral rationales, which were more effective in decreasing the magnitude of symptoms experienced by patients and increasing their independence during daily activities (17, 18). Recently, it has been shown that customized and supervised exercises are more beneficial than unsupervised (e.g., performed alone at home) or general fitness exercises (1924).…”
Section: Introductionmentioning
confidence: 99%
“…Supervised vestibular rehabilitation exercises seem superior to home exercises, where they provide better patient compliance. Furthermore, it allows the therapist to regularly assess patients' progress and provide them with feedback on their performance [56][57][58].…”
Section: Discussionmentioning
confidence: 99%